2021
DOI: 10.1088/1742-6596/1883/1/012147
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent control model of athletes’ training intensity based on big data analysis of physical fitness

Abstract: Based on the analysis of big data, this paper designs the intelligent control model of sports athletes’ training progress. By constructing the evaluation system of sports athletes’ training intensity, it improves the intelligent control algorithm of sports athletes’ training intensity, and ensures the operation effect of the intelligent control model of sports athletes’ training intensity. In order to verify the effect of the model, simulation experiments are carried out, and the results show that most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The 5G network services can improve communication performance and provide the best trade for linked IoT devices. Zhang [ 10 ] established an intelligent control technique for sports players' training development based on comprehensive data analysis. The intelligent control algorithm of sports athletes' training intensity was enhanced, and the operational efficacy of the intelligent control model of sports athletes' training intensity was secured, thanks to the development of the assessment system.…”
Section: Related Workmentioning
confidence: 99%
“…The 5G network services can improve communication performance and provide the best trade for linked IoT devices. Zhang [ 10 ] established an intelligent control technique for sports players' training development based on comprehensive data analysis. The intelligent control algorithm of sports athletes' training intensity was enhanced, and the operational efficacy of the intelligent control model of sports athletes' training intensity was secured, thanks to the development of the assessment system.…”
Section: Related Workmentioning
confidence: 99%
“…If scientific researchers want to obtain a scientific movement speed curve, they must reasonably allocate the whole speed and different speed stages to keep the speed movement of each 100-meter athlete relatively stable, and only when the speed change curve is relatively smooth, the fluctuation is small [30]. From a large number of papers, the author found that the speed change curve models of the world's top elite men's 100 m athletes are mainly in the form of "dam-type" curve model and "bimodal" curve model [31]. In order to show the change characteristics of the 100 m speed curve model of track and field sprinters in track and field championships more directly, this paper draws the 100 m speed curve models of preliminaries, semifinals, and finals in the competition, respectively (Figure 9).…”
Section: Analysis Of the Whole Speed Curve Model Of 100-metermentioning
confidence: 99%